Detection of transmissible gastroenteritis virus by RT-PCR and differentiation from porcine respiratory coronavirus - Paton, David (J Virol Methods, 1997)
An RT-PCR method was developed that amplified genetic material from the 5′ end of the S protein gene of both transmissible gastroenteritis virus (TGEV) and porcine respiratory coronavirus (PRCV), but discriminated between the two by the size of the product generated. A number of restriction endonuclease enzymes were assessed for recognition of the amplicons so produced. The assay was shown to detect viral RNA from all of the 26 different TGEV and PRCV isolates examined, covering a period from 1946 to 1996. Detection of TGEV in clinical specimens was possible using a spin column method to extract RNA and sensitivity was compared to virus isolation and antigen detection ELISA. The method could provide a means of confirming positive results from immunological screening tests such as FAT and ELISA, reducing the need for virus isolation and convalescent serology.